Investigation on the effect of ionic conductivity of SiO2 nanofiller in mg30 based gel elctrolyte. / Nur Hamizah Mohd Zaki - Mohd Zaki, Nur Hamizah (2010)
In this research, polymer plays the main role in composite polymer electrolyte (CPE) along with salt and nanofiller. The salt provides ions for conduction and the nanofiller use to enhance the ionic conductivity. Natural rubber grafted with 30% poly (methyl methacrylate) use as a polymer host in composite polymer electrolytes for application in electrochemical devices. The film was prepared by solution cast technique. Impedance spectroscopy technique was carried out in order to determine the electrical conductivity value. The highest conductivity of liquid electrolytes was 2.39x10"5 Scm"1 at 60 wt% of ZnCk. The polymer gel electrolyte was prepared by adding plasticizers propylene carbonate (PC). The highest ionic conductivity was 1.41xl0"3 Scm-1 at sample MG30+ 60 wt% ZnCl2+ PC+ 20 wt% ZnCl2.